Aspectos higiênico-sanitários, físico-químicos e microbiota lática de leite cru, queijo de coalho e soro de leite produzidos no Estado da Paraíba - Freitas, Wilma Carla de (2011)
The coalho cheese is a traditional product made in northeastern Brazil, is widely consumed in the state of Paraiba and knowledge of their indigenous microflora is of the fundamental importance. Thus, this study aim to: verify the microbiological and physical-chemistry characteristics of raw milk, whey and coalho cheese the three properties (A, B and C), respectively located in the regions of Paraiba and compare them with the legislation; to evaluate the profile of consumers of coalho cheese; isolate, characterize and identify lactic acid bacteria in these samples using two methods, comparing them and check the antimicrobial activity against these bacteria identified as Salmonella enterica, S. aureus and L. monocytogenes. Samples of raw milk and nine of cheese were submitted the following tests: standard plate count (SPC), the Most Probable Number (MPN) of total and thermotolerant coliforms, S. aureus, Salmonella; and analysis of pH, water activity, acid, protein, fat, total solids, nonfatty solids, fat in dry matter, humidity, ashes, chlorides and density. The samples of milk, whey and cheese, thermotolerant coliforms and S. aureus were present in numbers above the recommended level, indicating inadequate sanitary conditions of the raw milk and the final product. Regarding the physical-chemical analysis, was found high acidity in milk samples from the producers B and C and cheese samples were considered fat, high and very high humidity. The lactic acid bacteria counts of raw milk from producers B and C were in the order of 106 CFU/ mL in the whey and three producers of 107 CFU/mL, while cheese producer C obtained the highest counts (109 CFU/g). The 112 typical colonies of lactic acid bacteria were isolated and yours distribution of from the products were: Enterococcus, Lactococcus, Streptococcus and Leuconostoc. From a total of twenty isolates, twelve were identified by the API kit. The two methods used for comparison in the identification of genera, only 25% coincided and diverged with the majority of identifications performed by the second method of the Cogan et al., (1997). Of the twenty isolates, nineteen showed inhibition halos on three pathogenic bacteria, with inhibition zones 2 to 15 mm being the largest halos formed by Lactococcus lactis ssp lactis on S. enterica and S. aureus. However, the antimicrobial activity displayed by some lactic acid bacteria isolates suggest the possibility of its use against pathogens and can act as a barrier in the development of these micro-organisms and biological preservatives in coalho cheese.